For Organizational Communication that Promotes the Sharing of Tacit Knowledge - Oliveira, Márcio (2021)
Objectives - focusing the study's focus on sharing tacit knowledge in non-profit organizations (NPOs) in Portugal and taking as a case study the Portuguese volunteer firefighters (FBs), we listed as objectives ascertaining the main communicational barriers to tacit knowledge sharing and identify action strategies to be implemented by these organizations, with a view to promoting this communication. Design / methodology / approach - A literature review on the barriers to sharing tacit knowledge, namely in its communicational dimension, was followed by a qualitative study, carried out with 8 Portuguese volunteer fire brigades, which allowed an analysis of the prevalence of these barriers and the determination of the main measures to be implemented, with a view to combating them. Conclusions - It was possible to conclude which are the most prevalent communication barriers in these organizations and what measures to be implemented with a view to combating these barriers and promoting the sharing of tacit knowledge by increasing more effective communication. Research limitations - This research focuses exclusively on the sharing of tacit knowledge, not considering other forms of knowledge. As this is a case study, although with very heterogeneous organizations, it cannot be replicated for different realities. Originality / value - Studies in this area, aimed at the NPOs are scarce, as opposed to what happens in the private and public sectors. The case study option of organizations such as the Portuguese FBs, unique in their action and identity, accompanies the need, increasingly recognized by society, in enabling these organizations of competences for the best possible performance, in the face of the tragic events that have occurred in recent years in Portugal.